Korelasi antara Rasio Limfosit Neutrofil dan Nilai Ambang Batas Siklus RT-PCR pada Bayi Terinfeksi Covid-19 - Suryadi N. N. Tatura; Rifrita F. Halim (Universitas Sam Ratulangi, 2024)
Abstract: Covid-19 pandemic has been a new illness since the start of 2019 which was caused by SARS-CoV-2 coronavirus. In children, severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection has been linked to a multisystem inflammatory syndrome and coronavirus disease 2019 (Covid-19). This study aimed to obtain the correlation between the neutrophil-lymphocyte ratio (NLR) and the cycling threshold (CT) value (viral load) of RT-PCR for Covid-19 in infant patients. This was a descriptive and analytical study with a cross-sectional design. Secondary data were obtained from medical records of March 2020 to February 2022 at Prof. Dr. R. D. Kandou Hospital, Manado. Subjects were all infants admitted or born during the recording period, with suspected or confirmed Covid 19, including infants with mothers whose Covid-19 antigen tests were reactive. Data of age, gender, diagnosis, outcome CT value of RT-PCR test, and NLR were retrieved, and analyzed with Pearson correlation, meanwhile comparison based on gender and outcome of care using the independent T-test. All analyses were conducted with IBM SPSS 26.0. The results showed that the correlation between CT value and NLR was -0.361 with a p-value of 0.067. In conclusion, there is no significant correlation between CT value and NLR level with weak correlation. However, CT and NLR values appeared to be inversely associated; the higher the NLR value, the lower the CT value. Keywords: infants; Covid-19; cycle threshold of RT-PCR; neutrophil-lymphocyte ratio Abstrak: Pandemi Covid-19 menjadi penyakit baru sejak awal tahun 2019 sebagai akibat dari virus corona SARS-CoV-2. Pada anak, infeksi sindrom pernapasan akut parah coronavirus-2 (SARS-CoV-2) telah dikaitkan dengan sindrom inflamasi multisistem dan penyakit virus corona 2019 (Covid-19). Penelitian ini bertujuan untuk mengetahui hubungan antara rasio neutrofil-limfosit (NLR) dan nilai ambang batas siklus (CT) RT-PCR Covid-19 pada bayi. Jenis penelitian ialah deskriptif analitik dengan desain potong lintang. Data sekunder diperoleh dari rekam medis sejak Maret 2020 hingga Februari 2022 di RSUP Prof. Dr. R. D. Kandou Manado. Semua bayi yang dirawat atau lahir selama periode pencatatan, dengan suspek atau konfirmasi Covid-19, termasuk bayi dengan ibu yang tes antigen Covid-19-nya reaktif. Data yang dianalisis pada penelitian ini antara lain usia, jenis kelamin, diagnosis, nilai CT hasil tes RT-PCR, dan NLR. Analisis data yang dilakukan yaitu analisis deskriptif, korelasi Pearson, dan perbandingan berdasarkan jenis kelamin dan hasil perawatan dengan analisis uji t independen. Semua analisis dilakukan dengan software IBM SPSS 26.0. Hasil analisis menunjukkan nilai korelasi antara nilai CT dan NLR sebesar -0,361 (p=0,067). Simpulan penelitian ini ialah tidak terdapat hubungan bermakna antara nilai CT dan nilai NLR dengan korelasi yang lemah. Nilai CT dan NLR tampaknya berkorelasi terbalik dengan NLR yang lebih tinggi dikaitkan dengan nilai CT yang lebih rendah. Kata kunci: bayi; Covid-19; nilai ambang batas siklus RT-PCR; rasio neutrofil-limfosit